Upaya Meningkatkan Pendapatan Bank Melalui Optimalisasi Cross Selling Terhadap Pelanggan - Nuryadin, Endang (Journal the Winners: Economics, Business, Management, and Information System Journal, 2001)
The article explores some efforts to generate Bank’s income by optimalizing cross selling for is existing customers. After explaining background and clarifying that terminologies the paper starts with efforts and constraints of cross selling optimalization, those problem solutions, and how to promote the bank products.